The effect of functional mandibular advancement for adolescent patients with skeletal class II malocclusion on the TMJ: a systematic review and meta-analysis - Lan Ding; Rui Chen; Jiaxin Liu; Yuan Wang; Qian Chang; Liling Ren (BMC, 2022)
Abstract Objectives This study aimed to assess whether functional mandibular advancement (FMA) will cause temporomandibular joint disorders (TMD) or have side effects on temporomandibular joint (TMJ) in adolescent patients. Methods All searched databases, including PubMed, Web of Science, EMBASE, Cochrane Central Register of Controlled Trails and Scopus were searched. Gray literature and unpublished literature was also searched. Randomized controlled trails (RCT) and non-randomized studies of the effects of interventions (NRSI) directly observe the condition of adolescent patients' TMJ after finishing treatment will be considered to include in our study. According to Cochrane Handbook, Cochrane Collaboration risk of bias tool was used to assess the quality of included RCTs, and Risk of Bias In Non-randomized Studies of Interventions (ROBINS-I) tool was used to assess the quality of included NRSIs. Result Finally 18 researches were evaluated as eligible to include in this study. 5 of the studies were RCTs, 8 were NRSIs and 5 were systematic reviews. The data of RCTs and NRSIs were statistically pooled in meta-analysis. The number of samples under investigated among primary studies was 579 individuals,there were 80 patients who developed temporomandibular symptoms during or after treatment. But all the subjective symptoms disappeared during follow-up time. The statistical outcomes proved that patients received FMA didn't show more tendency to develop temporomandibular symptoms [I2 = 27%, OR = 0.54, 95%CI (0.33,0.87), p = 0.01]. Conclusion (1) TMJ symptoms may occur during the functional oral appliance wearing, but the symptoms will release or disappear after treatment or during the follow-up period. (2) Less convincing evidence indicates that slightly previous TMD and condyle-glenoid fossa relationship will be improved after treatment. (3) There is TMJ disc anterior displacement observed during treatment, but most of them will return to the normal position later. (4) Moderate evidence support that FMA will not have side effects on TMJ of adolescent patients.